Land laws for the future - Mohamad, Nor Asiah (2012)
Sustainable land development is a global agenda. New policies are being drafted from time to time to meet the planning and development expectation. Unfortunately, in many situations the laws are always one step behind. There are hundred laws dealing with land but there is doubtful as to the number of laws that promote sustainable development and thus, addressing land protection. Even if there are many, the effectiveness of some of the laws is yet to be seen in promoting green and sustainable agendas. This study is confined to the law dealing with land with special focus on the National Land Code and other laws that relate to land use, development and planning as well as land holdings. In doing so, several policies on land and case laws are referred in order to analyse the interpretation and the implementation of the laws. Some principles such as land is a state matter is also highlighted to gauge the implication of policy on the implementation of the laws and relate them to the success and failure in assuring sustainable land development. The research aims to accentuate the extent of which the land laws being the main reference for land policies remains relevant in meeting the new global agenda on sustainable development.